The christmas murder game eaudiobook - Benedict, Alexandra (Dreamscape Media, 2022)
Lily Armitage never intended to return to Endgame House—the grand family home where her mother died twenty-one Christmases ago—until she receives a letter from her aunt, asking her to return to take part in an annual tradition: the Christmas Game. The challenge? Solve twelve clues to find twelve keys. The prize? The deeds to the manor house. Lily has no desire to win the house. But her aunt makes one more promise: The clues will also reveal who really killed Lily's mother all those years ago. So for the twelve days of Christmas Lily must stay at Endgame House with her estranged cousins and unravel the riddles that hold the key not just to the family home but to its darkest secrets. However, it soon becomes clear that her cousins all have their own reasons for wanting to win the house—and not all of them are playing fair. As a snowstorm cuts them off from the village, the game turns deadly. Soon Lily realizes she's no longer fighting for an inheritance, but for her life.